The Use of Teacher Talks to Manage Students’ Feelings in Classroom Interaction - Elfrida Dewi Sukmawati; Ika Lusi Kristanti; Afi Ni'amah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2026)
Teacher talk plays an important role not only in facilitating learning but also in supporting students emotionally and creating a comfortable learning environment. This study aimed to explore the categories of teacher talk commonly used by an English teacher in a secondary school and how these categories contribute to managing students’ feelings during classroom interaction. This study adopted a qualitative method and applies the FLINT (Foreign Language Interaction) system by Brown (2001) as the main theoretical framework to classify teacher talk types and to explain its role in classroom interaction. The data were collected from two English class sessions using video recorder and observation checklists. The results showed that asks questions, praises or encourages, and gives directions were the most frequently used categories of teacher talk. Among them, deals with feelings, and jokes were found to contribute significantly to students’ emotional management. These types of talk helped reduce anxiety, boost students’ confidence, and create a more engaging classroom atmosphere. In summary, teacher talk functions not only as a means of instruction but also as an emotional support tool that contributes to positive classroom interaction. The findings assist English teachers of secondary schools to be more aware of the affective impact of their talk in class. Integrating supportive and encouraging language, even in small amounts, can enhance classroom interaction and students’ emotional well-being.